Examination of selected national policies towards mandatory folic acid fortification - Lawrence, Mark A; Chai, Weizhong; Kara, Raija; Rosenberg, Irwin H; Scott, John; Tedstone, Alison (Nutrition reviews, 2009)
The purpose of this paper is to present an examination of the contrasting policies towards mandatory folic acid fortification in six countries from different regions of the world. Three questions are addressed: 1) What is the policy of the country? 2) Why was the policy adopted? 3) What lessons have been learned? Policy contrasts among countries were assessed as reflecting different interpretations of the potential risks and benefits associated with folic acid fortification. Although commonalities were identified, it was considered unlikely that there could be a standard policy response for all countries. Instead, a country-by-country policy response based on national circumstances is indicated.